Exposure to nickel oxide nanoparticles induces pulmonary inflammation through NLRP3 inflammasome activation in rats - Cao Z (Dove Medical Press, 2016)
Zhengwang Cao,1 Yiliang Fang,1 Yonghui Lu,1 Fenghua Qian,2 Qinglong Ma,1 Mingdi He,1 Huifeng Pi,1 Zhengping Yu,1 Zhou Zhou1 1Department of Occupational Health, 2Department of Haematology, Southwest Hospital, Third Military Medical University, Chongqing, People’s Republic of China Abstract: With recent advances in the manufacture and application of nickel oxide nanoparticles (NiONPs), concerns about their adverse effects on the respiratory system are increasing. However, the underlying cellular and molecular mechanisms of NiONP-induced pulmonary toxicity remain unclear. In this study, we focused on the impacts of NiONPs on pulmonary inflammation and investigated whether the NLRP3 inflammasome is involved in NiONP-induced pulmonary inflammation and injury. NiONP suspensions were administered by single intratracheal instillation to rats, and inflammatory responses were evaluated at 3 days, 7 days, or 28 days after treatment. NiONP exposure resulted in sustained pulmonary inflammation accompanied by inflammatory cell infiltration, alveolar proteinosis, and cytokine secretion. Expression of Nlrp3 was markedly upregulated by the NiONPs, which was accompanied by overexpression of the active form of caspase-1 (p20) and interleukin (IL)-1β secretion in vivo. NiONP-induced IL-1β secretion was partially prevented by co-treatment with a caspase-1 inhibitor in macrophages. Moreover, siRNA-mediated Nlrp3 knockdown completely attenuated NiONP-induced cytokine release and caspase-1 activity in macrophages in vitro. In addition, NiONP-induced NLRP3 inflammasome activation requires particle uptake and reactive oxygen species production. Collectively, our findings suggest that the NLRP3 inflammasome participates in NiONP-induced pulmonary inflammation and offer new strategies to combat the pulmonary toxicity induced by NiONPs. Keywords: NLRP3 inflammasome, nickel oxide nanoparticles, inflammation, cytokines